Virtual Reality Body Exposure Therapy for Anorexia Nervosa. A Case Report With Follow-Up Results - Porras-Garcia, Bruno; Serrano-Troncoso, Eduardo; Carulla-Roig, Marta; Soto-Usera, Pau; Ferrer-Garcia, Marta; Figueras-Puigderrajols, Natàlia; Yilmaz, Lena; Onur Sen, Yigit; Shojaeian, Nazila; Gutiérrez-Maldonado, José (Frontiers in Psychology, 2020)
Objective Exposure-based therapies such as mirror exposure may help to improve the results of classic cognitive behavioral therapy in anorexia nervosa (AN). Virtual reality (VR)-based procedures provide interesting novelties for targeting body-related concerns. This study aimed to provide preliminary evidence of the usefulness of a VR body exposure therapy in a patient diagnosed with AN. Method Fear of gaining weight (FGW), body anxiety, drive for thinness, body image disturbances, body mass index and body-related attentional bias were assessed before and after the intervention, as well as 5 months later. Five sessions of VR body exposure therapy were included within the standard course of cognitive behavioral therapy. The sessions involved a systematic and hierarchical exposure of the patient to a virtual representation of her own silhouette, with the body mass index of the avatar progressively increasing in subsequent sessions. Results After the intervention, there was a clear reduction in AN symptoms such as the FGW, drive for thinness, body-related anxiety and dissatisfaction. Body mass index values rose continuously during the intervention and reached healthy levels. Finally, there was a notable change in the dysfunctional body-related attentional bias. Almost all these improvements were maintained after 5 months, except for the FGW. Conclusion To the best of our knowledge, this study is the first to focus on treating the FGW and body-related concerns in AN using a VR-based paradigm. To pursue this study further and assess the effectiveness of this new VR software, larger controlled clinical trials are needed.